RASIO PROFITABILITAS, MANAJEMEN RISIKO DAN MANAJEMEN MODAL KERJA PADA SEKTOR PERBANKAN SYARIAH DAN KONVENSIONAL - Muhammad Abdurraafi; Nani Ernawati; Yoyok Prasetyo; Mochammad Rizaldy Insan Baihaqqy (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study examines profitability ratios, risk management, and working capital management in Islamic and conventional banking sectors. Using a comparative approach, the analysis focuses on financial performance indicators such as Return on Equity (ROE), Non-Performing Financing (NPF)/Non-Performing Loan (NPL), and Current Ratio to identify differences and similarities between the two banking models. The Mann-Whitney U Test is applied to assess whether there are significant differences in these financial ratios between Islamic and conventional banks.Methods: The findings indicate that profitability ratios, risk management strategies, and working capital management differ significantly between the two banking sectors. Islamic banks have a unique financial structure due to Sharia compliance, which influences risk and capital management, including maintaining a more controlled NPF level. Meanwhile, conventional banks rely on interest-based financial mechanisms, shaping their profitability and liquidity strategies differently, including NPL and Current Ratio management to ensure financial stability.Results: The results of this study contribute to a deeper understanding of the financial performance of Islamic and conventional banks. These insights can serve as a guide for policymakers, investors, and banking institutions in making more strategic decisions regarding operations, risk mitigation, and financial planning. Keyword: Profitability Ratio, Risk Management, Working Capital Management, Return on Equity (ROE), Non-Performing Financing (NPF/NPL), Current Ratio (CR